Influence of landscape and vegetation characteristics on herpetofaunal assemblages in Gulf Coastal Plain pine forests. Issue 3 (22nd February 2022) - Royal, Ethan J.; Greene, Daniel U.; Miller, Darren A.; Willson, John D.
Abstract: Longleaf pine ( Pinus palustris ) savanna characterized by open‐canopy, diverse herbaceous vegetation, and high amounts of bare soil once covered much of the southeastern United States Coastal Plain. The unique structural and vegetative conditions of this ecosystem support endemic reptiles and amphibians that have declined as longleaf pine forests have been lost or degraded. Private working pine ( Pinus spp.) forests managed for timber production now occur throughout the southeastern United States and have replaced much of the historical longleaf pine savanna. The examination of herpetofaunal (reptile, amphibian) communities in private working loblolly pine ( P. taeda ) landscapes, particularly in the western Gulf Coastal Plain is lacking. Using repeated field surveys and hierarchical community occupancy models, we examined occupancy and species richness of herpetofauna across 81 sites spanning gradients of management practices, vegetative conditions, and soil composition in northwestern Louisiana, USA, 2017–2019. Young pine stands (<6 yr) exhibited structural characteristics most similar to mature longleaf pine reference sites (>30 yr), while mid‐aged stands (13–26 yr) often featured closed canopy and dense midstory. Vegetation conditions varied widely depending on landscape characteristics and site‐specific disturbance regimes. We documented 43 species of herpetofauna, including 9 open‐pine‐associated species. Occupancy of open‐pine‐associated herpetofauna was positively associated with open‐canopy and understory conditions, and sandy soil area. Sites providing open‐canopy conditions were often occupied by open‐pine‐associated species regardless of overstory type and disturbance method. Overall richness of herpetofauna was greatest at sites with moderate canopy cover outside of sandy soil regions. Working pine landscapes in the western Gulf Coastal Plain can support diverse herpetofaunal assemblages, including open‐pine‐associated species, when management practices maintain open‐canopy conditions on sandy, upland soils. More broadly, our results provide insight into how forest management practices affect herpetofauna and may guide practices that can contribute to conservation value of working pine forests. Abstract : This study highlights the potential and limitations of pine forests under varying management regimes and featuring different landscape characteristics to support a range of herpetofaunal species. This research will guide management decisions targeting herpetofaunal conservation on a regional and site‐specific basis by illustrating the influence of site‐specific structural conditions and larger‐scale landscape characteristics on an area's ability to support a variety of species.